2007
DOI: 10.1590/s1415-54192007000200017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco da mordida aberta anterior na dentadura decídua completa em pré-escolares na cidade de Natal/RN

Abstract: Objetivo: estimar a prevalência da mordida aberta anterior na dentadura decídua completa em crianças pré-escolares da cidade de Natal/RN e a associação desta a alguns fatores de risco. Metodologia: este estudo caracterizou-se por ser do tipo transversal e utilizou como elementos amostrais 366 indivíduos na idade de 5 anos na fase de dentadura decídua completa. A mordida aberta anterior, variável dependente, foi categorizada em presente e ausente. No que se refere às variáveis independentes estas foram dividida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
13
3
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 16 publications
6
13
3
11
Order By: Relevance
“…3 Sex was not associated with malocclusion, as confirmed in previous studies. 6,25 Whereas a number of authors argue that children with greater purchasing power and those whose mothers have a lower schooling level are more likely to develop malocclusion due to greater access to and frequency of pacifier use, 29,30 no significant associations were found in the present study between socioeconomic indicators and malocclusion, in agreement with findings reported in previous studies. 6,9 It seems that another factor unassociated to social class has occurred, namely the greater participation of women in the workforce, with a consequent reduction in breastfeeding and greater susceptibility to the adoption of nonnutritive sucking habits.…”
Section: Resultssupporting
confidence: 91%
“…3 Sex was not associated with malocclusion, as confirmed in previous studies. 6,25 Whereas a number of authors argue that children with greater purchasing power and those whose mothers have a lower schooling level are more likely to develop malocclusion due to greater access to and frequency of pacifier use, 29,30 no significant associations were found in the present study between socioeconomic indicators and malocclusion, in agreement with findings reported in previous studies. 6,9 It seems that another factor unassociated to social class has occurred, namely the greater participation of women in the workforce, with a consequent reduction in breastfeeding and greater susceptibility to the adoption of nonnutritive sucking habits.…”
Section: Resultssupporting
confidence: 91%
“…Similar outcomes in children of the same age have been found in other regions of the Brazil 15,17 . Other studies have found a prevalence of more than 30% 4,18,19 .…”
supporting
confidence: 85%
“…The same was confirmed in the other regions. 4,17,20,21 the differences in variables related to gender (p = 0,163), socioeconomic condition (p = 0,527) and degree of education of the person responsible for the child's welfare (p = 0,528) were not statistically significant. An investigation conducted in Bauru has found higher prevalence in female children 19 .…”
Section: This Research Was Approved By the Research Ethics Committee mentioning
confidence: 91%
See 1 more Smart Citation
“…7,13,38 Differences were found between the genders in regards to the prevalence of malocclusion, differing from the findings of other authors. 20,36 This difference can be explained by the higher prevalence of sucking habits observed in girls, since the presence of malocclusion was strongly associated with such habits.…”
Section: Resultsmentioning
confidence: 99%